Thinking outside the box: how planning can revolutionize public procurement - Pederneiras, Marcleide Maria Macêdo; Gomes, Franskran Nunes; Cardoso, Silvia Karina Alves Barros (Seven Editora, 2023)
The objective of this article is to stimulate discussion about the planning that involves public contracting during the bid preparation stage. This is because it is during this stage that the administration will determine its needs for the acquisition of goods, services, works, and information technology solutions, as well as their respective quantification. In this article, the following problem was adopted: does planning the public contracting process mean an increase in bureaucracy, or a guarantee that the procedure will be carried out efficiently? To this end, it was defined as a general objective to analyze whether planning public hiring bureaucratizes or guarantees efficiency in the public hiring process, and as specific objectives, (i) describe the public hiring process in the Brazilian legal system; (ii) understand the importance of the planning stages for efficient hiring; (iii) demonstrate that planning contributes to efficient hiring, but that it does not represent the ideal of sluggish bureaucracy. The hypothetical-deductive research method was used, and the research technique adopted was bibliographic, based on the reading and summarizing of works, norms, and publications on the theme. As a result, it was observed that the most essential tool to ensure the quality of public contracts is planning. However, it must be done properly, taking into account the principles of legality, efficiency, and advantage, as well as the obligations of both the public manager and all other parties governing public contractsDOI: https://doi.org/10.56238/devopinterscie-055